Mallotus bullatus (Euphorbiaceae), a new species from Southwest China based on morphological characters and phylogenetic evidence - Jiang-Hong Yu; Zheng-Ren Chen; Ming-Tai An; Deng-Li Yu; Feng Liu; Jian Xu; Yu-Bin Tang; Yi-Ran Wang; Hua-Kai Zou (PhytoKeys)
Mallotus bullatus M.T.An & J.H.Yu, sp. nov. (Euphorbiaceae), a species new to science discovered in Guizhou, China, is described and illustrated here, and its phylogenetic position among other Mallotus species is presented. Morphological, micro-morphological, and molecular evidence is presented as attestation of its novelty. The new species morphologically resembles M. philippensis var. reticulatus and M. philippensis var. philippensis, but it clearly differs by having bullate leaf surfaces (vs. not bullate), leaf margins entire or nearly so (vs. entire or nearly so in M. philippensis var. philippensis and coarsely serrate in M. philippensis var. reticulatus), leaf margins sometimes bearing red glands (vs. red glands absent), 5 sepals in staminate flowers (vs. 3–4 in M. philippensis var. philippensis and 4 in M. philippensis var. reticulatus), fruits with spines (vs. spines absent in M. philippensis var. philippensis and present in M. philippensis var. reticulatus), and abaxial leaf epidermal scattered and clustered vein hairs 0.1–0.8 mm long (vs. 0.04–0.28 mm long in M. philippensis var. philippensis and 0.05–0.1 mm long in M. philippensis var. reticulatus). Molecular phylogenetic analysis (BS = 100% / BS = 96%, PP = 1 / PP = 1) provides strong evidence supporting M. bullatus as a new species within the genus Mallotus and supports its placement in M. sect. Philippinenses as sister to M. philippensis.